HUBUNGAN SELF CONTROL TERHADAP PERILAKU KONSUMTIF BELANJA ONLINE PADA MAHASISWA - Nita Nilam Sari; Nur Irmayanti (Fakultas Psikologi Universitas Wijaya Putra, 2021)
Students are one of the young people who are still unstable, need recognition from the social environment, and experience instability. In this case, the ability to control themselves or restraint becomes weak, so they tend to act on emotions. One of the problematic behaviors is buying behavior. This study aims to determine the relationship between student self-control with online shopping consumption behavior. This study uses quantitative methods with research design using correlational quantitative. The population in this study were teenage students with a subject of 70 teenage students. The sampling technique used is purposive sampling. The data collection tool uses a self-control scale and consumptive behavior. Data analysis using product moment correlation coefficient. The results showed a correlation of 0.983 with a significance of 0.000 because of the significance.